ANALISIS MAJAS DALAM LIRIK LAGU HINGGA UJUNG WAKTU KARYA EROSS CANDRA - Siswanti Puji Lestari; Syaima Nur Amalia; Sary Sukawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Any lyrics in the song must have a specific purpose that wish to be conveyed to his listeners. Therefore, every song lyrics will be delivered with an interesting language. The writing of the song lyrics will not regardless of the style of the language poets includes either word choice or sentence structure, diction, or figure of speech. This research will describe the figure of speech which featured in the lyrics of the song "until the end of Time" by Eross Candra through stylistical research. Assessment against this research object using the document analysis techniques by reading the lyrics to a song that will be analyzed, understood the meaning of the lyrics of the song, then find words containing figure of speech in the song lyrics and describe it. The result of stylictical research in the lyrics “Until end of Time” indicates that the song's lyrics contain a wide variety of figure of speech, including comparison; simile, metaphor, personification, hyperbole, contradiction, and parallelism or repetition of words at the end.